2015
DOI: 10.4103/2230-8229.163038
|View full text |Cite
|
Sign up to set email alerts
|

Medical emergencies encountered in dental clinics: A study from the Eastern Province of Saudi Arabia

Abstract: Objectives:To report the prevalence of medical emergencies in dental clinics and self-perceived competence of dentists in the Eastern Province of Kingdom of Saudi Arabia (KSA).Materials and Methods:In this cross-sectional study, a self administered questionnaire was distributed to a random sample of 198 dentists working in private and government dental clinics in the Eastern Province of KSA. The respondents were approached twice to ensure good participation in the study.Results:One hundred and forty-five denti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 19 publications
2
14
1
Order By: Relevance
“…Moreover, only 51.4% reported that they could perform CPR. This is comparable to a previous project conducted in Saudi Arabia, which reported only 45% of dentists felt competent to perform CPR (Alhamad et al, 2015). Other studies have likewise reported the majority of dentists felt they are unable or unprepared to provide CPR, BLS or first aid in an emergency (Arsati et al, 2010;Stafuzza et al, 2014;Varma et al, 2015).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Moreover, only 51.4% reported that they could perform CPR. This is comparable to a previous project conducted in Saudi Arabia, which reported only 45% of dentists felt competent to perform CPR (Alhamad et al, 2015). Other studies have likewise reported the majority of dentists felt they are unable or unprepared to provide CPR, BLS or first aid in an emergency (Arsati et al, 2010;Stafuzza et al, 2014;Varma et al, 2015).…”
Section: Discussionsupporting
confidence: 77%
“…Vasovagal syncope is often cited as the most commonly occurring ME in dental practice (Alhamad et al, 2015;Müller et al, 2008). However other MEs that may occur include: cardiac arrest, anaphylaxis, airway obstruction, stroke, as well as hypoglycaemic, asthmatic, and epileptic episodes (Leelavathi, Reddy, Elizabeth, & Priyadarshni, 2016;Müller et al, 2008).…”
Section: Centre For Chronic Disease Prevention and Health Promotion mentioning
confidence: 99%
See 1 more Smart Citation
“…There was a study by Mostafa et al published in 2015 and looked into medical emergencies in dental offices in the eastern province of Saudi Arabia [ 11 ]. Never the less it is well documented that the Saudi population is suffering from a high incidence of Diabetes and cardiovascular diseases [ 12 ][ 13 ] which again may predispose to medical emergencies during dental treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The statistical analysis was done using Decision Analyst 2.00 12 . The eleven attributes shown in figure no 2, have been analyzed for two groups of data.…”
Section: Discussionmentioning
confidence: 99%